X-ray test to evaluate the physiological potencial of Platypodium elegans Vog. Seeds (Fabaceae) - Paradelo Gomes, Kever Bruno (2016)
The objective of this work was to evaluate the internal morphology of Platypodium elegans Vog. seeds through the X-ray tests and to verify their relation with germination. 200 radiographic images were taken of each group and the tests were taken with the seeds set at 28.0 cm from the source of x-rays. Next, the seeds were classified according to their internal morphology as seen in the radiographic images. Three categories of seeds were established: full, empty and partially full. For each seed category, germination tests were performed. Statistical design in factorial 3x3, with three groups and three categories. From the results obtained in this work, the use of x-ray test with Platypodium elegans Vog. seeds is promising in quality of seed groups detection, assisting in empty and partially full seeds separation, invalidating their immediate use or storage. The x-ray test, in 26 kV for 1.2 seconds intensity was efficient in Platypodium elegans Vog. internal morpholy evaluation. There is a relationship between the internal morphology of seeds and the results of the germination test. The importance of a methodology of easy implementation, aiming at estimating the germinative power of the groups of seeds, was proved by the x-ray tests in seeds of Platypodium elegans Vog. and can also be used for the analysis of the internal morphology of other forest species.